Incidencia de las estrategias comunicacionales del ministerio del interior en el comportamiento de las barras de barcelona y emelec en la ciudad de Guayaquil - Vicuña Pita, Jennifer Janeth (2015)
This study aims to determine the impact of communication strategies Interior Ministry in preventing violence in the stadiums of Ecuador. Also offer a proposal according to the problem, from a communication perspective. This research will analyze and evaluate the current situation, while providing alternative solutions to a problem that exists in the city of Guayaquil and creates insecurity in the public who prefer to watch a football game in the comfort of your home to attend a frightened stadium being attacked……